Hybridity in the governance and delivery of public services - Savignon, Andrea B.; Gnan, Luca; Hinna, Alessandro; Monteduro, Fabio (Bingley, UK Emerald Publishing, 2018)
This book seeks to answer the unsolved questions related to hybrid organisations, adopting a multifaceted approach focussing on different national contexts, including the UK, Italy, Australia, and Sweden, as well as global organisations. Authors consider policy sectors including humanitarian aid, local transport, healthcare, and welfare services.
1. How History Challenges Current Thinking On Hybridity: The Effects of Hybridity on Londons Transport 1933-1948; James Fowler. 2. Transparency, Accountability and Control in Hybrid Organizations: The Case of Enterprises Owned by Local Government; Gissur O. Erlingsson, Anna Thomasson and Richard Ohrvall 3. The Role of Boards of Directors in Transparency and Integrity in State-Owned Enterprises; Ilenia Cecchetti Veronica Allegrini and Fabio Monteduro 4. The Influence of Human Resources Practices On Corruption Behavior in Humanitarian Aid; Soha Bou Chabke and Gloria Haddad 5. Adapting to Person-Centred Care: Changes in Caring Organizations in The Australian Disability Sector; Bruce Gurd, Cheryll Lim and Ellen Schuler 6. New Public Management and Hybridity in Healthcare: The Solution or The Problem?; Roman Andrzej Lewandowski and Łukasz Sułkowski 7. The Institutional Governance of Global Hybrid Bodies: The Case of the World Anti-Doping Agency; Jean-Loup Chappelet and Nicolien Van Luijk 8. Strategic Philanthropy in Foundations: The Board Members Perspective; Giacomo Boesso and Fabrizio Cerbioni 9. Collaboration Between For-Profit and Non-Profit Organizations: Some Insights into The Social Doctrine of the Church; Paolo Andrei, Federica Balluchi and Katia Furlotti 10. Boundary-Spanning Leadership in Hybrid Networks: A Case Study of English Local Safeguarding Children Boards; Adina Dudau Alvise Favotto and Georgios Kominis
Includes bibliographical references and index
Keywords: Intergovernmental cooperation -- Case studies; Municipal services -- Case studies; Corporate governance; Government business enterprises; Public administration -- International cooperation